Crystal-chemical aspects of the roméite group, A2Sb2O6Y, of the pyrochlore supergroup. (December 2017) - Bosi, Ferdinando; Christy, Andrew G.; Hålenius, Ulf
Abstract: Four specimens of the roméite-group minerals oxyplumboroméite and fluorcalcioroméite from the Långban Mn-Fe deposit in Central Sweden were structurally and chemically characterized by single-crystal X-ray diffraction, electron microprobe analysis and infrared spectroscopy. The data obtained and those on additional roméite samples from literature show that the main structural variations within the roméite group are related to variations in the content of Pb 2+, which is incorporated into the roméite structure via the substitution Pb 2+ →A 2+ where A 2+ = Ca, Mn and Sr. Additionally, the cation occupancy at the six-fold coordinated B site, which is associated with the heterovalent substitution B Fe 3+ + Y ☐→ B Sb 5+ + Y O 2-, can strongly affect structural parameters. Chemical formulae of the roméite minerals group are discussed. According to crystal-chemical information, the species associated with the name 'kenoplumboroméite', hydroxycalcioroméite and fluorcalcioroméite most closely approximate end-member compositions Pb2 (SbFe 3+ )O6 ☐, Ca2 (Sb 5+ Ti) O6 (OH) and (CaNa)Sb2 O6 F, respectively. However, in accord with pyrochlore nomenclature rules, their names correspond to multiple end-members and are best described by the general formulae: (Pb, #)2(Sb, #)2 O6 ☐, (Ca, #)2 (Sb, #)2 O6 (OH) and (Ca, #)Sb2 (O, #)6 F, where '#' indicates an unspecified charge-balancing chemical substituent, including vacancies.